161 Effect of Direct Fed Microbials on Apparent Nutrient Digestibility, Fecal Microbial Population, and Blood Metabolites in the Moderately Exercised Horse. (10th April 2018) - Phillips, C A; Cavinder, C A; Memili, E; Rude, B J; Smith, T
Abstract: Performance horses are subject to intensive training and competition that results in physiological stress. Stress can lead to maladies such as behavioral stereotypes, colic, and gastric ulceration which may hinder performance. In poultry and cattle, blood cortisol has been shown to be altered by probiotic supplementation. The mixed results of probiotic supplementation on apparent digestibility and blood metabolites warrants further study. Six stock-type horses (8.13 ± 3.48 yr; 489.77 ± 50.280 kg) were used in a completely randomized design lasting 42 d to determine the effect of direct fed microbials (DFM) on the apparent digestibility of nutrients, fecal microbial population, and blood metabolites in moderately exercised horses. Horses were fed 0.5% BW/d of control (CON) grain or grain with DFM added and 1.5% BW/d of a 50/50 bermudagrass and alfalfa mix hay. The DFM contained Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium thermophilum, Enterococcus faecium, and Saccharomyces cervisiae at a rate of 25.1 x 10 9 cfu/g of grain, averaging 61.5 x 10 12 cfu/d. After a 21-d washout period, horses were gradually transitioned to 1 of 2 diets for a 21-d treatment period. Horses were worked 3 d/wk for 1 h at 30% walk, 55% trot, and 15% canter to simulate moderate exercise requirements (NRC, 2007). Blood was collected pre-and post-exercise for handheld lactate analysis and serum cortisol using a commercial RIA. Fresh per rectum fecal samples were collected in a staggered manner (n = 4/d) during the last 2 d of each washout and treatment period. Samples were plated, the top 3 isolates were phenotypically identified, and sensitivities determined. During the last 72 h of each treatment period, a total fecal collection was performed utilizing modified fecal collection bags. Statistical analysis was performed using the MIXED procedure of SAS with horse within diet as a random block effect and as a subject of repeated measures. Apparent ADF digestibility approached significance (P = 0.064) for DFM. Observational assessments found that DFM experienced smaller increases in potentially pathogenic bacteria excretion. Resting lactate was decreased (P = 0.036) with DFM. Post exercise cortisol was not affected (P = 0.944) by diet. Mean heart rate approached significance (P = 0.075), while DFM had faster HR than CON (105.04 vs. 100.08 beats/min, respectively). Results indicate DFM may have an impact on nutrient digestibility and microbial populations in exercise-stressed horses. The concentration of DFM supplemented yielded no negative physiological results.